(untitled) (Research, Society and Development, 2023)
In December 2019, the SARS-CoV-2 disease began in China, in 2020 it was considered a pandemic by the World Health Organization. The immune system fights infections such as COVID-19, however, during pregnancy there is an atypical behavior of immunity to maintain adequate fetal development, as pregnant women are at risk for COVID-19. The objective of the present study was to analyze maternal mortality rates in the context of the SARS-CoV-2 Pandemic, in the North of Brazil. This is a cross-sectional, retrospective and analytical epidemiological study on maternal mortality between the years 2016 to 2020 and 2019 to 2020, in the context of COVID-19 in the North of Brazil, using data from the health literature and reported cases in the Notifiable Diseases Information System. In the period analyzed, there were 1,211 maternal deaths in the Region, with emphasis on the states of Pará (49%) and Amazonas (26%), despite annual variations, the occurrences between the states were little changed, the average between the years of 2016 to 2020. There was a 133% increase in indirect obstetric maternal deaths in 2020 compared to 2019. According to the study’s analysis, the obstetric mortality rate increased in 2020, the initial period of the pandemic, with emphasis on for the states of Roraima and Amapá, which had the highest percentage increase, in addition, maternal deaths due to indirect supplementary causes in 2020 in relation to previous specific years, highlighted by the Pandemic.